Lexical Innovations Introduced Through the Cultural Lexeme ‘Zhady’ in Khoja Ahmed Yasawi’s Hikmet - Azhibekova М.Е.; Sagidolda Г.; Abdimaulen Г.А. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
This study aims to analyze the linguistic unit “zhady” in Hikmets by Khoja Ahmed Yasawi. The concept of cultural lexicon is defined, and the frequency of usage of this unit in Yasawi’s Hikmets, which explains the sources of our spiritual values and conveys religious understanding in a way appealing to the people’s worldview, is examined. It is concluded that each cognitive linguistic unit requires individual analysis. The research was conducted within lexical-semantic and cognitive frameworks. Based on the transcribed version of the Samarkand (Zaleman) manuscript presented in R. Sydyk’s monograph “The Language of Yasawi’s Hikmets,” the study analyzes the cultural lexeme “zhady” and demonstrates its function as a “linguistic unit of memory retention.” It examines the various uses of the linguistic unit “zhady” in Yasawi’s language. The terms “cultural code,” “national code,” “cultural lexicon,” “lexical innovations,” and “cultural lexicon” are explained. Drawing on the works of both domestic and foreign Yasawi scholars, the study demonstrates that it identifies the mechanisms for expanding the lexical inventory within cognitive linguistics. The study explains the phonetic differences between the translation and the manuscript using a historical-comparative method. The practical significance of the study lies in the possibility of applying its results in theoretical courses on lexicology and cognitive linguistics, as well as in seminars related to Yasawi studies.